Original Research Article The Multilevel Influence of Individual, Parental, and School Factors on the Nutritional Status of Obese Children in Banda Aceh: A PLS-SEM Analysis - Kurniasih, Rahmah; Nina, Nina (Jurnal Publikasi Kesehatan Masyarakat Indonesia, 2025)
The study's purpose was to identify the main things impacting the nutrition of school-aged children, with a special focus on kids who are overweight or obese. The study utilized a specific method called the Disjoint Two-Stage Approach in PLS-SEM, guided by the socio-ecological theory. Our study group had 87 children who were over-nourished or obese, along with their parents and school principals. When we looked at the results, we saw that individual factors had a big positive effect on children's nutrition status (β=0.341;p=0.000). Also, parent factors showed the biggest effect, which was also positive (β=0.500;p=0.000). However, school factors showed a negative effect, but it was not strong enough to be important (β=−0.086;p=0.293). This means that while schools are there, their direct influence in this study was not as clear. The R-Square value was 0.430.This means that these three things together (child's own habits, parent part, and school part) can show 43% of why children's food status is different. These findings make it clear that it is very important to have nutrition help that focuses on the family and the child. It is also needed to make schools stronger in helping children eat healthy through clear rules and programs